Implementing Splunk : a comprehensive guide to help you transform big data into valuable business insights with Splunk 6.2 /: a comprehensive guide to help you transform big data into valuable business insights with Splunk 6.2. (2015) - Bumgarner, Vincent; (Software consultant), Miller, James D
No abstract available